Vulnerability to child sexual abuse : NOABS tool (2023)
Background: The prevalence of child sexual abuse shows a result of 19% in females and 8% in males. Objective: The main aim of this study, is to identify the level of vulnerability and risk of sexual abuse in children between 6 to 13 years old with the NOABS tool. Participants and Setting: 684 children between the ages 6 and 13 from the Simón Araujo school in Sucre, Co-lombia. Methodology: The methodology used in this study has a descriptive approach and data was analyzed with a quantitative strategy. Results: After analyzing the data, it shows a 5.3 % high vulnerability (VA), (VA) female (F) 4.3 %, 6.5 % male (M), (VA) family context 16.1 %, social 14.9 %, school 8.2 %. Conclusions: Other researches allow to compare these results in order to have a clear idea about the levels of vulnerability and risk of abuse validating the NOABS game.